Image Encryption Using Orthogonal Hill Cipher Algorithm - Madhusudhan Reddy, K.; Itagi, Anirudh; Dabas, Saransh; Kamala Prakash, Bonam (International Journal of Engineering and Technology, 2018)
The Hill Cipher algorithm is a practical algorithm which requires only preliminary knowledge of matrices which makes it quite useful. But, for decrypting the encoded information the key matrix needs to have an inverse (The key matrix needs to be invertible) or else it is impossible to decrypt the given information. The main objective of our paper is to introduce an unorthodox and improved version of Hill Cipher which will make encryption and decryption of an image easier. This paper has diverged from the conventional method by using an orthogonal matrix (where the transpose of a matrix is equal to its inverse) as our key matrix. This method is faster and easier as finding the transpose of a matrix is much simpler than finding the inverse of a given matrix and hence, facilitating the process of faster execution. To further break down the process into an even simpler one, we have added a few more constraints. To show its application, we have used this method to encrypt images using MatLab.Â Â